Peningkatan keterampilan menyajikan data dalam bentuk diagram melalui model Problem Based Learning kelas IV sekolah dasar - Veranita Intan Palupy; Sukarno Sukarno; Muhammad Ismail Sriyanto (Didaktika Dwija Indria, 2019)
The purpose of the reseach is to improve the skills of presenting data in the form of diagrams through the use of the Problem Based Learning model in fourth grade students of SD N Laweyan No. 54 Surakarta 2018/2019 school year. Classroom Action Research is conducted in two cycles, each cycle consisting of two meetings with four stages, namely planning, action, observation, and reflection. The subjects of this study were teachers and fourth grade students, amounting to 34 students. This study uses observational techniques, interviews, documentation, and tests. Data analysis using interactive data analysis with steps of data reduction, data presentation, and conclusions. The data validity test technique uses source triangulation and technical triangulation The results showed that the average score of pre-action class scores of 17.97 with 0% classical completeness increased to 75.88 with 61.76% classical completeness in the first cycle and increased again to 87.25 with a classical completeness of 88.24% in cycle II. Based on the results of the study, it can be concluded that through the application of the Problem Based Learning model can improve the skills of presenting data in the form of diagrams in class IV SD N Laweyan No. 54 Surakarta 2018/2019 school year.